The Impact of Feedback on Self-rated Driving Ability and Driving Self-regulation Among Older Adults - Ackerman, Michelle L. (Oxford University Press, 2011)
In 129 community-dwelling older adults, feedback regarding qualification for an insurance discount (based on a visual speed of processing test; Useful Field of View) was examined as a prospective predictor of change in self-reported driving ability, driving avoidance, and driving exposure over 3 months, along with physical, visual, health, and cognitive variables. Multiple regression models indicated that after controlling for baseline scores on the outcome measures, failure to qualify was a significant predictor of increased avoidance over 3 months (p = .02) but not change in self-rated driving ability or exposure. Female gender (p = .03) was a significant predictor of subsequent lower self-rated driving ability. Overall, the findings of this study provide support for the role of feedback in the self-monitoring of older adults’ driving behavior through avoidance of challenging driving situations but not through driving exposure or self-rated driving ability.